Detection of Norovirus and Rotavirus in Children under Five Years During Winter 2012-2013 in Mosul Province - Mohamed, Nadira Salman; Hameed, Mohammed Fadhel; Al-Rubai, Haider Khadum (Al-Nahrain Journal of Science, 2018)
The identifying the viral agents such as norovirus genogroup I (NVGI), norovirus genogroup II (NVGII) and rotavirus (RV) is critical to the development of effective preventive measures. This study aimed to determine the prevalence of common enteric viruses in children